Impact of International Family Transitions: A Systematic Literature Review of International Research - Koini, Catherine M.; Jindal-Snape, Divya; Robb, Anna J. (International Journal of Educational and Life Transitions, 2022)
A systematic literature review of international empirical research was conducted to understand the impact of international family transitions on families’ experiences, wellbeing and facilitating/inhibiting factors of successful international transitions. The review covered the period 2000–2021. Using the EPPI-Centre approach, authors included 26 studies in the review that met the inclusion criteria. Synthesis of the findings suggested that, children and parents experienced international transitions differently. While children were primarily concerned with social issues, parents worried about managing family and work commitments. The findings relating to wellbeing outcomes were mixed, and we cannot say with confidence whether family wellbeing was impacted by international transitions. There was a dearth of literature examining what constitutes a successful international transition experience. The review demonstrated the challenge of viewing international transitions in a linear manner and suggests international transitions should be conceptualised as complex, multi-dimensional, dynamic and ongoing in nature. This review is the first to bring together children and parents’ experiences, wellbeing outcomes and facilitating/inhibiting factors using the Multiple and Multi-dimensional Transitions (MMT) theory. As a result, it provides some unique insights and makes an original contribution.